GEOGRAPHY OF WORK BY INTEGER - Thomaz Junior, Antonio [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2018)
The validity of the process of capital productive restructuring imposes harmful changes that are occurring in the context of work, tuned to the resulting reordering, which, since the late 1980, guided new lines of social conflict, not restricting only the classic format capital x work, but involving other forms of class domination, in order to imply new perspectives on the classical boundaries - deeply revised for the worse, with the labor reform, already in place, after December 2017, in Brazil - what is working in the countryside (employed, peasant) and work in the city (employees, self-employed, intermittent, informal), under different social relations of production and job. In these early years of the second decade of the 21st century, our research retake previous studies within the CPR, supported on the fact that the barbarism that sealed the endless process of reconciliation with the irreformability of capital, with the purpose of eliminating misery and poverty that befalls in most of humanity in the 20th and 21st centuries, only provided feedback to the different stages of class domination. In all geography of work, our attentions are primarily geared to address critically the continued extraction of surplus labor and the procedures linked to this structural element to so many other forms of domination, subordination and control of the work, in addition to the wage regulations.
Keywords: Geography of work; Productive restructuring; Plasticity of the work; CPR; Continuing education; Emancipation